Il Patrimonio mondiale religioso inaccessibile. Conservazione e fruizione ampliata - Trematerra, Adriana (Restauro Archeologico, 2023)
The contribution proposes the study of the Meteora Monasteries in Greece, a complex of Orthodox places of cult situated on rocky promontories, included in the World Heritage list in 1988. While these areas originated as a result of the desire of some monks to build isolated and inaccessible places of cult, with the opening to tourism and the attribution of a new museum function, the original characteristic aimed at isolation is now a distant prerogative. In the context of expanded and inclusive use, these areas present high criticalities. The contribution intends to question the possibilities offered by the discipline of restoration for the recovery of some elevators and funicular railways, added in recent years and currently in disuse or only usable by the monastic community, in order to guarantee each individual the possibility of being able to enjoy an heritage with a high historical, architectural and landscape value.